MACHINE-TO-MACHINE COMMUNICATIONS IN INDUSTRIAL IOT PROTOCOLS AND SECURITY: English - P., Chitralingappa; Shaik, Nazeer; B., Harichandana; C. Krishna Priya; Sumalatha, P. (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Machine-to-machine (M2M) communication has become a cornerstone of modern industrial networks, facilitating seamless data exchange between devices without human intervention. This technology supports the Industrial Internet of Things (IIoT) and enables intelligent, autonomous operations in sectors like manufacturing, logistics, and energy. Despite its advantages, M2M communication introduces critical security and protocol challenges due to its reliance on large-scale, heterogeneous networks. This paper reviews current M2M communication protocols, examines security concerns specific to industrial contexts, and proposes a framework to enhance protocol reliability and security. Experimental results demonstrate the effectiveness of the proposed framework in minimizing potential security risks while maintaining operational efficiency.